EVEKTIFITAS PEMANFAATAN LABORATORIUM BIOLOGI STKIP PGRI SUMATERA BARAT TERHADAP PENINGKATAN PEMAHAMAN SISWA MAN 1 PADANG PARIAMAN - Nursyahra Nursyahra; Rival Yuhendri; Diana Susanti (Universitas PGRI Sumatera Barat, 2019)
Biology laboratory has an important role in the learning process. One of them is to train students' skills in understanding the biological material they have learned in class. STKIP biology laboratory PGRI West Sumatra consists of basic laboratories, botanical laboratories and zoology laboratories and hospitals. Where each laboratory has different specifics, basic laboratories that lead more to general subjects are mediocre in general biology, basic chemistry and others. While in the botany laboratory it is more directed to the subject of plants such as plant morphology, plant anatomy, low plant taxonomy and others. While the zoology laboratory is more focused on subjects such as, animal structure, animal physiology, animal development, animal taxonomy and others. While the wire house is often used for courses in agricultural cultivation, plant physiology, plant ecology and others. MAN I Padang Pariaman School is a school that works closely with biological study programs. One form of collaboration carried out with learning to laboratories in biology study programs with the guidance of lecturers and teaching assistants. The results obtained after the learning students receive a lot of what they learn from what they have seen and they get from the lecturer.